A qualitative investigation of lay perspectives of diagnosis and self-management strategies employed by people with progressive multiple sclerosis. (May 2017) - Frost, Julia; Grose, Jane; Britten, Nicky
This article explores how people with progressive multiple sclerosis give meaning to their experiences. It builds upon the self-management literature, which has captured the tension between the desire for retaining normalcy and the increasing burden of self-management associated with chronic disease progression. This repeat interview study is empirically grounded in 28 interviews with 14 people with progressive multiple sclerosis. We identified gender differences in diagnosis-seeking which impacted subsequent sense-making. Male respondents found a diagnosis of multiple sclerosis difficult to come to terms with, and an enduring sense of loss or anger could inhibit further sense-making. A diagnosis of multiple sclerosis was more difficult to obtain for women respondents, and any sense of certainty that diagnosis provided framed their subsequent sense-making strategies. The complex sequelae of multiple sclerosis require that self-management strategies are both contextual and timely, although even the most accomplished self-managers can lose their sense of self with neurodegeneration. Disease progression can be associated with suicidal ideation, suggesting the need for greater dialogue to ensure that people with multiple sclerosis are adequately supported to fulfil their quality of life at all stages of neurodegeneration. These lay perspectives emphasise the articulation of affect rather than the rendering of a medical diagnosis, although diagnosis may provide a degree of certainty in the short term. The ethos of self-management ensures people attempt to retain their sense of 'normality' and existent social roles for as long as possible, but this ethos can negate both one's ability to self-manage and the management of self.